Analisis Kemampuan Pemecahan Masalah Matematis Siswa SMP dalam Menyelesaikan Soal Cerita pada Materi Persamaan Linear Satu Variabel (PLSV) - Fransisca, Ayu (Polinomial : Jurnal Pendidikan Matematika, 2025)
This study was conducted with the aim of knowing the mathematical problem solving ability of junior high school students in solving story problems on the material of linear equations of one variable (PLSV). The research method used is a qualitative method with descriptive analysis. This research was conducted on VIII grade students in one of the public junior high schools in Karawang Regency. A total of 15 students as research subjects and data obtained using test instruments in the form of 4 items of mathematical problem solving ability on the material of linear equations of one variable. Based on the results of the study, the mathematical problem solving ability of grade VIII junior high school students in Karawang Regency seen from the indicator of identifying the adequacy of data to solve problems is quite high, on the indicator of making a mathematical model of a problem and solving it is moderate, but on the indicator of choosing and applying strategies to solve mathematical problems and checking the correctness of the results and answers is still low.